Mathematical Literacy Ability Reviewed From Self-Efficacy In Realistic Mathematics Education Approach - Faozi, Rizal; Wardono, Wardono; Haryani, Sri (Universitas Negeri Semarang, 2020)
Mathematical literacy is one of the abilities of students assessed by PISA studies in terms of formulating, applying, and interpreting mathematical problems in various contexts. This ability is believed to increase if students are given structured training to solve problems close to their daily lives. Structured training can be done with a project or expository approach and both have their own strengths in eliciting student self-efficacy. The study aimed to analyse students' mathematical literacy ability reviewed from their self-efficacy in Realistic Mathematics Education (RME) model both in project and expository approach. The research was a mixed methods study with sequential explanatory design. There were 60 students, selected by simple random sampling, equally distributed in the experimental class with project based learning and control class with expository based learning. Data of students’ mathematical literacy were collected by using tests and were triangulated with observational dan document data analysis. The results showed that the average mathematical literacy ability of the experimental class is better than that of the control class. The mathematical literacy were influenced by students’ self-efficacy variables of 53.5%. The effect of self-efficacy on mathematical literacy of the way students solve problems was discussed.